Machine Learning in Image Analysis and Pattern Recognition - Kumar, Munish; Sharma, R. K.; Sethi, Ishwar (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is to chart the progress in applying machine learning, including deep learning, to a broad range of image analysis and pattern recognition problems and applications. In this book, we have assembled original research articles making unique contributions to the theory, methodology and applications of machine learning in image analysis and pattern recognition.